Impact of Behavioral Biases on Investment Decisions - Kandel, Madan; Basnet, Bhupindra Jung; Aryal, Mahendra (DEPAN, 2024)
This study investigates the influence of behavioral biases on individual investment decisions in the Nepalese equity market, focusing on five key biases: representative, herding, overconfidence, anchoring, and regret aversion. A survey of 401 investors from the Kathmandu Valley was conducted using structured questionnaires. Data analysis employed descriptive and inferential statistical methods, including regression analysis, revealing that all five biases significantly impact investment decisions, with representative bias being the most influential. The findings underscore the reliance on cognitive heuristics, such as perceived patterns and initial reference points, alongside a tendency to adopt conservative strategies driven by regret aversion. The study highlights gaps in financial literacy and information access as barriers to rational investment behaviors.The research provides novel insights by linking behavioral finance theories to empirical data in a developing economy context, emphasizing the role of biases in shaping market dynamics. Practical implications include the need for financial literacy programs, enhanced information dissemination platforms, and decision-support tools to mitigate bias-driven errors. This study contributes to the growing body of literature on behavioral finance in emerging markets and offers actionable strategies to improve investment outcomes.